Descarte e reaproveitamento do lixo eletrônico nas oficinas de reparação na cidade de São Gabriel RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The facilities that the electronic technology provides us are immense. They are part of the day to day of people and is often not perceived, precisely because it is rooted in their daily lives. Only when an electronic device stops working does one realize how much it lacks. The fact that Brazil has more cell phones than people is an example of the popularization of electronics, not to mention other devices such as computers, televisions, DVDs, video games, etc. Advertising around electronic devices further boosts consumption, often leading to the early disposal of devices considered "obsolete" simply because they are out of fashion. The low life of some versions of these devices on sale has also raised doubts about the so-called "sheduled obsolescence". This work takes an approach on this from the point of view of the profession of Electronics Technician, citing examples of devices that leave to be desired when the question is precisely the durability, in addition to addressing the reverse logistics and reuse of electronic components in other devices in repair shops in the municipality of São Gabriel. Through interviews in the establishments, the objective was to evaluate the economic feasibility of repairing some electronic devices. In addition, the behavior of the professionals in the face of the programmed obsolescence, which leads to the early disposal of the products and their final destination, was analyzed. Through the conclusion of this work, it is hoped to elaborate new perspectives for the reuse of electronic components and an adequate destination for these wastes.
Keywords: Logística reversa; Resíduos eletrônicos; Obsolescência programada; Reverse logistic; Electronic waste; Sheduled obsolescence; CNPQ::CIENCIAS SOCIAIS APLICADAS